The Development of Winged Angels in Early Christian Art - Martin, Therese (Espacio Tiempo y Forma. Serie VII, Historia del Arte, 2001)
The first representations of angels in Early Christian art showed a being visually indistinguishable from man. This study undertakes to explain the sudden apperarance of winged angels in the late fourth century within its religious and historical contexts The model for winged angels was Nike, an unusual choice given that Victory was conceived of as a female, while angels were decidedly male. Las primeras representaciones de angeles en el art paleocristianno fueron de un ser visualmente indiferenciado del hombre. Este estudio pretende explicar la aparicion subita de angeles con alas, a fines del siglo IV, dentro de ese particular contexto historicoreligioso. El modelo de angel con alas fue Nike, una eleccion inusual si se tiene en cuenta que la Victoria fue concebida como mujer, mientras que los angeles eran indudablemente masculinos.